Photodetection Enhancement via Dipole–Dipole Coupling in BA2MAPb2I7/PEA2MA2Pb3I10 Perovskite Heterostructures - Bin Han; Bingtao Lian; Qi Qiu; Xingyu Liu; Yanren Tang; Mengke Lin; Shukai Ding; Bingshe Xu (Inorganics, 2025)
Two-dimensional (2D) hybrid organic–inorganic perovskites (HOIPs) have attracted considerable attention in optoelectronic applications, owing to their remarkable characteristics. Nevertheless, the application of 2D HOIPs encounters inherent challenges due to the presence of insulating organic spacers, which create barriers for efficient interlayer charge transport (CT). To tackle this issue, we propose a BA2MAPb2I7/PEA2MA2Pb3I10 bilayer heterostructure, where efficient interlayer energy transfer (ET) facilitates compensation for the restricted charge transport across the organic spacer. Our findings reveal that under 532 nm light illumination, the BA2MAPb2I7/PEA2MA2Pb3I10 heterostructure photodetector exhibits a significant photocurrent enhancement compared with that of the pure PEA2MA2Pb3I10 device, mainly due to the contribution of the ET process. In contrast, under 600 nm light illumination, where ET is absent, the enhancement is rather limited, emphasizing the critical role of ET in boosting device performance. The overlap of the PL emission peak of BA2MAPb2I7 with the absorption spectra of PEA2MA2Pb3I10, alongside the PL quenching of BA2MAPb2I7 and the enhanced emission of PEA2MA2Pb3I10 provide confirmation of the existence of ET in the BA2MAPb2I7/PEA2MA2Pb3I10 heterostructure. Furthermore, the PL enhancement factor followed a 1/d2 relationship with the thickness of the hBN layer, indicating that ET originates from 2D-to-2D dipole–dipole coupling. This study not only highlights the potential of leveraging ET mechanisms to overcome the limitations of interlayer CT, but also contributes to the fundamental understanding required for engineering advanced 2D HOIP optoelectronic systems.